Potential fishing ground interpretation using overlay technique for Aceh sea water - Mirna Ria Andini
Aceh is an Indonesian province in Sumatra Island, an area surrounded by the ocean with an area of 296000 krn '. The large of Aceh's seawater and the abundant fishery potential, make it as one of the most important economic sectors in Aceh. While the Aceh seawater has a huge fishery potential but the fisheries are only fulfilling 37% of their maximum potential. Various methods have been assessed in determining the fishing ground by utilizing the remote sensing image interpretation technique as one of the solution to detect the potential fishing ground accurately. The oceanography parameter has the ability to determine the location of fishing such as sea surface temperature and chlorophyll-a concentration. The data ASCII and data images is extracted from data sea surface temperature and chlorophyll-a concentration Aqua and Terra MODIS satellites using SeaDAS application. And the data interpolation module is employed for constructing new images of sea surface temperature and chlorophyll-a from data ASCII. The major improvement of this study is centered on determining the potential fishing ground in Aceh seawater that has two oceanography parameters with sea surface temperature values below 29°C and value of chlorophyll-a concentration above 0.5 mg/rrr'. Opacity reduction techniques of the layer in data overlay module are up to 50% which make the location of fishing in Aceh seawater clearer and more detailed. The experimental results show that the average values of data of chlorophyll¬a concentration from Aqua MODIS satellite are 0.02 mg/m ' to 0.37 mg/m' and from Terra MODIS satellite are 0.19 mg/rrr' to 0.47 mg/m'. The average values of data of sea surface temperature from Aqua MODIS satellite are 27.78"C to 30.62"C and from Terra MODIS satellite are 27.78"C to 30.62"C. Based on the study, the contour maps and the information obtained from the satellite were overlaid to obtain potential fishing ground in the Aceh seawater. It was discovered that potential fishing ground is prominently located along the coastal areas of Aceh seawater. The results also indicated in October, November and December 2016 the highest potential fishing ground is found in most of all of the Aceh seawater.